ANALISIS DINI KANKER RAHIM DAN PENANGANANNYA UNTUK MENINGKATKAN TARAF HIDUP PEREMPUAN - Adella Syahputri; Ferosa Ulandari; Annisa Marinda Syach Rizal; Isabela Olga; Viyoli Mardhatillah Karepesina (Universitas Pahlawan Tuanku Tambusai, 2023)
Uterine cancer is one of the diseases suffered by women because it is related to the uterus or womb. Acute uterine cancer that is not handled properly can cause death in women. So this must be addressed immediately to improve the standard of living of women, considering that women's roles are quite complex in life. This is what encourages researchers to conduct research on early analysis of uterine cancer and its treatment to improve women's lives. The purpose of this research is to find out how to analyze and treat uterine cancer in women so that women's living standards can increase. The research method used is qualitative with data collection techniques through library research. The collected research data will then be analyzed so that the results of the research are known, that early analysis of uterine cancer can be carried out by self-detect with various symptoms that might indicate uterine cancer, such as feeling pain in the abdomen, experiencing bleeding outside the menstrual period, experiencing bleeding during menstruation. menopause, excessive vaginal discharge, stomach feels enlarged, where the symptoms that occur are also followed by systemic symptoms such as decreased appetite, decreased body weight, feeling weak and anemia. Meanwhile, the way to handle it is through diet, surgical removal of the uterus, chemotherapy, radiology, and so on.